The effect of bank levy introduction on commercial banks in Europe - Karolina Puławska (Journal of Risk and Financial Management, 2021)
We evaluated the effects of the bank levy (BL) on the profitability of commercial banks and the balance sheet reconstruction, and the shifting of banks' activities into countries with lower BL rates after BL introduction. Moreover, we investigated the effects of the Basel III and Single Resolution Fund (SRF) introduction on the amount of BL payment. We compared two different BL designs: the Hungarian and the German versions. The results clearly pointed to the negative effect of BL introduction on the ROA of larger Hungarian commercial banks and of smaller commercial banks in Germany. Moreover, the results showed that the introduction of the BL did not influence loan activity in Hungary. However, it decreased the value of the loans from German commercial banks. The results showed that commercial banks in Hungary prefer to restructure their balance or shift assets among different locations or entities to decrease the bank levy. The research findings also showed that Hungarian commercial banks decreased the value of paid BL after the Basel III introduction. On the other hand, the results also showed that the value of paid BL in German commercial banks increased after the Basel III and SRF introduction, especially in larger banks.
Keywords: 330; bank levy; Basel III; commercial banks; profitability; Single Resolution Fund